A Test for Discriminating Between Members of the Odd Weibull-G Family of Distributions - Boikanyo Makubate (The Scientific World Journal)
The Odd Weibull-G (OWG) family of distributions has been discussed earlier in the literature. This family of distributions provides a “better fit” in certain practical situations. In a similar fashion, the OWG family of distributions is defined in this article. A method of moments estimator based on the maximum entropy principle is proposed for the discrimination of two members of the OWG family of distributions.